2014
DOI: 10.2337/db14-0337
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein APPL2 Inhibits Insulin-Stimulated Glucose Uptake by Interacting With TBC1D1 in Skeletal Muscle

Abstract: Insulin stimulates glucose uptake by promoting the trafficking of GLUT4 to the plasma membrane in muscle cells, and impairment of this insulin action contributes to hyperglycemia in type 2 diabetes. The adaptor protein APPL1 potentiates insulin-stimulated Akt activation and downstream actions. However, the physiological functions of APPL2, a close homolog of APPL1, in regulating glucose metabolism remain elusive. We show that insulin-evoked plasma membrane recruitment of GLUT4 and glucose uptake are impaired b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 43 publications
4
35
1
2
Order By: Relevance
“…Although pS237-TBC1D1 and pT596-TBC1D1 are 14-3-3 binding sites, insulin did not increase the ability of TBC1D1 to bind 14-3-3 [17]. Insulin increased pS235-TBC1D1 and binding of the adaptor protein containing PH domain, PTB domain and leucine zipper motif 2 (APPL2) to TBC1D1 in myocytes and mouse EDL [44]. In myocytes overexpressing APPL2, the binding of TBC1D1 to APPL2 required pS235-TBC1D1 and attenuated insulin-stimulated pT596-TBC1D1 and glucose uptake [44].…”
Section: Tbc1d1: Insulin-stimulated Glucose Transport By Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Although pS237-TBC1D1 and pT596-TBC1D1 are 14-3-3 binding sites, insulin did not increase the ability of TBC1D1 to bind 14-3-3 [17]. Insulin increased pS235-TBC1D1 and binding of the adaptor protein containing PH domain, PTB domain and leucine zipper motif 2 (APPL2) to TBC1D1 in myocytes and mouse EDL [44]. In myocytes overexpressing APPL2, the binding of TBC1D1 to APPL2 required pS235-TBC1D1 and attenuated insulin-stimulated pT596-TBC1D1 and glucose uptake [44].…”
Section: Tbc1d1: Insulin-stimulated Glucose Transport By Musclementioning
confidence: 99%
“…Insulin increased pS235-TBC1D1 and binding of the adaptor protein containing PH domain, PTB domain and leucine zipper motif 2 (APPL2) to TBC1D1 in myocytes and mouse EDL [44]. In myocytes overexpressing APPL2, the binding of TBC1D1 to APPL2 required pS235-TBC1D1 and attenuated insulin-stimulated pT596-TBC1D1 and glucose uptake [44]. Cells expressing a T596D-TBC1D1 phospho-mimic mutant were protected from APPL2 overexpression-induced insulin resistance.…”
Section: Tbc1d1: Insulin-stimulated Glucose Transport By Musclementioning
confidence: 99%
“…As adaptors, APPLs contain multiple protein and membrane‐binding modules, allowing docking of target proteins on specific membrane domains in the cell . APPLs can bind directly to membrane lipids, receptors and signaling molecules to coalesce the players and generate responses at specific membrane domains or cell compartments . In the context of the more well‐studied isoform APPL1, the N‐terminal membrane‐curvature BAR (Bin‐amphiphysin‐Rvs) domain linked to a PH domain and a C‐terminal phosphotyrosine‐binding domain bind to the signaling kinases Akt and PI3K, recruiting them for a variety of activated receptors .…”
mentioning
confidence: 99%
“…On the other hand, adiponectin modulates the dissociation of the APPL1/APPL2 heterodimers, which can also be triggered by insulin. Interestingly, Cheng et al 22 demonstrated that APPL2 inhibits insulin-stimulated glucose uptake in skeletal muscle. In this study, only the OTR/up group increased the hepatic levels of APPL2, which may be linked to the increased phosphorylation of the insulin receptor substrate 1 (IRS-1) at serine 307 3 , a molecular marker directly related to insulin signaling pathway impairment 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that APPL1 can limit the interaction between Akt and TRB3 in mouse liver tissue, which is accompanied by an increase in the membrane translocation of APPL1, Akt activation, and enhancement in response to insulin stimulation 22,23 . Also, adiponectin also stimulates APPL1 in mouse hepatocyte cells with activation of another class of proteins, the p38 mitogen-activated protein kinases (p38MAPK), which activates glucose transporters protein.…”
Section: Discussionmentioning
confidence: 99%